GEOSYNTHETIC REINFORCEMENT FOR EMBANKMENTS OVER DEGRADING DISCONTINUOUS PERMAFROST SUBJECTED TO PRESSTRESSING - M. C. Alfaro; J. A. Blatz; J. Graham (International Association of Lowland Technology, 2006)
Failures of road embankments on discontinuous permafrost commonly occur during thawing of the foundation soil. As an approximation, weak zones created by thawing of discontinuous permafrost can be considered as ‘voids’ within the foundation. Geosynthetic reinforcements have been used to bridge these ‘voids’ and provide support to the embankment fill. This paper presents results of a numerical investigation on the effects of prestressing geosynthetics to enhance their reinforcement effect, and thus reduce deformations of embankments over discontinuous permafrost. The study used the commercially available computer program, FLAC. Numerical analysis illustrates that prestressing geosynthetic reinforcement can be effective in controlling deformations and reducing the possibility of collapse of road embankments on degrading discontinuous permafrost.